Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

New species of Planchonella (Sapotaceae): one from Borneo and three from New Guinea - Ulf Swenson; Jennifer Kearey; Kent Do; Timothy M. A. Utteridge (Kew Bulletin, 2026)
Summary Planchonella is the largest genus in subfamily Chrysophylloideae (Sapotaceae) and includes 97 described species distributed from the Seychelles to Hawaii with the greatest species diversity in Australia, New Caledonia and New Guinea. There are approximately an additional ten taxa that do not easily conform with known species limits, and/or have been identified by molecular methods as new to science. We describe here four new species, P. cerebrifructa Swenson from Borneo and P. hispida Swenson, P. surculiflora Swenson and P. takeuchii Swenson from New Guinea, all with distinctive autapomorphic characters. Planchonella cerebrifructa is readily distinguished by its velvety, wrinkled young fruit, very similar to the complex, folded appearance of a brain’s surface. Planchonella hispida has hispid indumentum of long, Y-shaped trichomes, in decreasing density along the midrib and on the secondary, tertiary and quaternary venation. Planchonella surculiflora sets inflorescences on lateral shoots, often with one or two leaves borne between the villose flowers. Finally, Planchonella takeuchii , although the flowers are unknown, can be recognised by its characteristic glabrous foliage of broadly elliptic leaves with a tapering apex, short petioles (± 5 mm long) and tertiary leaf venation perpendicular to the primary and secondary veins. Now, with the description of these four species, the genus Planchonella includes 101 described species.

Two new species of Tapeinosperma (Primulaceae-Myrsinoideae) from Papua New Guinea and the Solomon Islands - Timothy Utteridge; Brendan Lepschi; Kipiro Damas (Kew Bulletin, 2025)
Two species of Tapeinosperma new to science are described from Papua New Guinea and the Solomon Islands: T. longipedicellatum Utteridge, Damas & Lepschi and T. purpureum Utteridge, Damas & Lepschi. Each species is illustrated, and a preliminary conservation status is given.

Expanding Ventilago to incorporate Smythea: new combinations in Ventilagineae (Rhamnaceae) based on novel sequence data and phylogenetic analysis - Henry Miller; Daniel Cahen; Félix Forest; Nattanon Meeprom; Pirada Sumanon; Timothy M. A. Utteridge (Kew Bulletin, 2025)
Summary Ventilagineae (Rhamnaceae) is a tribe of palaeotropical climbing plants, comprising two genera: Smythea and Ventilago . Previous studies have established the monophyly of the tribe, but the relationships within it remain unclear. This research includes six species of Smythea and seven species of Ventilago in a molecular phylogeny using the Angiosperms353 probe set. The results show that Ventilago is paraphyletic, with Smythea nested within it. To resolve this issue, we propose to merge Smythea into Ventilago . To achieve this, we make six new combinations and one new name in Ventilago as well as resurrecting five names previously published in Ventilago but subsequently transferred to Smythea . In addition, we typify Ventilago .

A synopsis of the genus Maesa (Primulaceae) in New Guinea - Pirada Sumanon; Wolf L. Eiserhardt; Henrik Balslev; Timothy M. A. Utteridge (Kew Bulletin, 2025)
Summary The genus Maesa in New Guinea is revised. Thirty-nine species are accepted in this study and a key to species (including incompletely known taxa) is presented; four new species, M. begoniifolia, M. pilosopapuana, M. serratifolia, and M. tagulensis are described, and a neotype is selected for the widespread Indonesian species M. tetrandra . Distribution, habitat, phenology and detailed taxonomic notes are provided, and the conservation status of each species is estimated based on IUCN criteria.

Towards a Flora of New Guinea: Oleaceae. Part 2, eight new species of Chionanthus - Ruth Kiew; Timothy M. A. Utteridge (Kew Bulletin, 2025)
Summary Chionanthus is the largest genus of Oleaceae in New Guinea and, of its 17 species on the island, eight are new species described and illustrated here. Its high level of endemism, 70% (12 species), is typical of the New Guinea flora. Most of these new species are restricted to Papua New Guinea but this is likely to be an artefact of lower collecting intensity in Indonesian New Guinea. However, the 17 species do not reflect the biodiversity of New Guinea Chionanthus, as there are already a further 15 – 20, unnamed, putative species in herbarium collections that are too incomplete to enable their formal description.

The genus Hypobathrum (Rubiaceae) in Thailand - Sawita Yooprasert; Jordan Bilsborrow; Timothy M. A. Utteridge (Kew Bulletin, 2024)
Summary The genus Hypobathrum in Thailand is revised, based on the morphological characters found in herbarium specimens from Thailand and neighbouring countries including Bangladesh, Myanmar, Cambodia and Peninsular Malaysia. In this study, three species of Hypobathrum are recognised, among them, H. venulosum is a newly recorded species in this region. An identification key is provided for the species, along with descriptions, synonyms, distribution ranges and vernacular names (if available).

Island area, isolation and climate effects upon flower traits in a megadiverse archipelago - Liam A. Trethowan; Laura Jennings; Gemma Bramley; Marie Briggs; Ruth Clark; Sally Dawson; Max Fontaine; Charlie Heatubun; Gwilym Lewis; Eve Lucas; Alison Moore; Laura Pearce; et al. (Journal of Biogeography, 2024)
Aim Flower traits are critical to the mutualistic networks that underpin ecosystem function. However, the broad‐scale drivers of flower traits are unclear. Using the megadiverse islands of Malesia, we test three hypotheses: (1) Flower size, openness and colourfulness (i.e. the trend from white to colourful flowers) will decrease with increasing temperature, but not with increasing precipitation seasonality. (2) Flower size, openness and colourfulness will increase with island area, and decrease with isolation. (3) Models parameterised by climate, rather than non‐climatic island characteristics will have the greatest predictive capacity as climate affects both pollinator communities and energetic/physiological constraints upon flower traits. Location Fourteen Malesian islands. Taxon Angiosperms. Methods We applied Bayesian phylogenetic models of occurrence for >2500 species in 400 m elevation bands, across islands, as a function of flower trait interactions with either climatic variables or islands characteristics. We compare predictive capacity of models based on climate versus island characteristics using Leave One Out‐Cross Validation. Results All six flower traits examined varied with at least temperature, precipitation seasonality, island area and isolation. Flowers are larger in cold environments. The lowland tropics are mostly inhabited by white flowered species. At cold high elevations, red and pink flowered species are more frequent whereas green and purple flowered species increase in the drought‐prone seasonally dry tropics. Flower openness declined with precipitation seasonality and increased with isolation. Models parameterised by climate performed best for perianth length, red and white flowers, whereas pink flowers and flower openness were better predicted using island characteristics. Main Conclusions There are relationships between flower traits and climatic gradients within Malesia. However, island characteristics have also left a legacy upon current flower trait distributions. These island biogeographical impacts are likely key for the eco‐evolutionary drivers of flower traits.

A new species of Lasjia (Proteaceae) from Sulawesi: Lasjia griseifolia Utteridge & Brambach - Timothy M. A. Utteridge; Liam A. Trethowan; Matilda J. M. Brown; Seth Ratcliffe; Jack Plummer; Fabian Brambach; Himmah Rustiami (Kew Bulletin, 2024)
Summary Lasjia griseifolia Utteridge & Brambach, a member of the Proteaceae, is described and illustrated as a new species from the Indonesian island of Sulawesi. The new species is similar to L. erecta , also from Sulawesi, and morphological differences between the taxa are discussed; a line illustration and detailed notes on the conservation status are provided.

Editorial - Timothy M. A. Utteridge (Kew Bulletin, 2024)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Reduction of Blinkworthia (Convolvulaceae) based on multilocus phylogenetic reconstruction and resurrection of a species from synonymy revealed by phenetic analyses - Pantamith Rattanakrajang; Pirada Sumanon; Paweena Traiperm; George Staples; Timothy Utteridge (Kew Bulletin, 2022)

Out of New Guinea? Two new species of Zygogynum (Winteraceae) extend the genus west of Lydekker’s and Wallace’s Lines - Timothy M. A. Utteridge; Himmah Rustiami (Kew Bulletin, 2022)
Summary The Winteraceae comprise 100 – 130 species in five to nine genera. The genus Zygogynum is currently thought to have a Papuasian-Pacific distribution and is only known from the western Pacific islands (New Caledonia, Vanuatu and the Solomon Islands), Australia and New Guinea, including the far western Bird’s Head Peninsula, but is not yet recorded from islands to the west of the Sahul Plate and the biogeographic boundary of Lydekker’s Line. Here, two new species of Zygogynum are described from west of both Wallace’s and Lydekker’s Lines. Zygogynum moluccanum is described from the Moluccan islands of Indonesia, and Z. sundaicum , a new species and generic record for the Sunda shelf, is described from the northern part of the Malaysian State of Sarawak in Borneo. In addition to descriptions and illustrations of the new species, the generic delimitation, fossil record and potential dispersal agents of Zygogynum are discussed.

A revision of Ziziphus (Rhamnaceae) in Borneo - Daniel Cahen; Jessica Rickenback; Timothy M. A. Utteridge (Kew Bulletin, 2021)
Summary The genus Ziziphus (Rhamnaceae) is revised for Borneo. 13 species are recognised using morphological evidence, including three new endemic species: Ziziphus cuspidata , Z. domatiata and Z. puberula . Borneo is therefore the island with the greatest known diversity of Ziziphus species. The area surrounding Mount Kinabalu is particularly diverse, with nine species occurring in Ranau. Two new varieties of Z. borneensis are also described here, Z. borneensis var. ranggam and Z. borneensis var. velutina , five new synonyms are established, including the placement of Z. elmeri as a synonym of Colubrina beccariana . A taxonomic treatment, including a preliminary IUCN conservation status assessment, is presented for each species and variety.

Taxonomy and morphology of Thalictrum (Ranunculaceae) in New Guinea - Renata Borosova; Timothy M. A. Utteridge; André Schuiteman (Kew Bulletin, 2021)
Summary The genus Thalictrum L. in New Guinea is revised based on morphological evidence. Full descriptions of the genus and the four taxa recognised are given. Two species are recognised: Thalictrum papuanum , widespread across New Guinea, and a new species described here; T. umbraticola , endemic to west New Guinea. Two new varieties are described: Thalictrum papuanum var. acutisegmentum and T. papuanum var. laticarpellum. One new synonym of Thalictrum papuanum var. papuanum is established: T. papuanum var. oranjense . Keys to the taxa and distribution maps, as well as preliminary conservation assessments, are provided.

Editorial - Timothy Utteridge (Kew Bulletin, 2021)

Metal‐rich soils increase tropical tree stoichiometric distinctiveness - Liam A. Trethowan; Benjamin Blonder; Endang Kintamani; Deden Girmansyah; Timothy M. A. Utteridge; Francis Q. Brearley (Plant and Soil, 2021)
Background and aims Ultramafic soils have high metal concentrations, offering a key opportunity to understand if such metals are strong predictors of leaf stoichiometry. This is particularly relevant for tropical forests where large knowledge gaps exist. Methods On the tropical island of Sulawesi, Indonesia, we sampled forests on sand, limestone, mafic and ultramafic soils that present a range of soil metal concentrations. We asked how variation in 12 soil elements (metals and macronutrients) influenced leaf stoichiometry and whether stoichiometric distinctiveness (the average difference between a species and all others in a multivariate space, the axes of which are the concentrations of each leaf element) is influenced by increasing soil metal concentrations. Results Positive correlations between corresponding elements in soils and leaves were only found for Ca and P. Noticeably, soil Cr had a negative effect upon leaf P. Whilst most species had low stoichiometric distinctiveness, some species had greater distinctiveness on stressful metal-rich ultramafic soils, generally caused by the accumulation of Al, Co, Cr or Ni. Conclusions Our observation of increased stoichiometric distinctiveness in tropical forests on ultramafic soils indicates greater niche differentiation, and contrasts with the assumption that stressful environments remove species with extreme phenotypes.

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

Notes on Erycibe (Convolvulaceae) from Thailand - Phongsakorn Kochaiphat; Syahida-Emiza Suhaimi; George W. Staples; Timothy M. A. Utteridge; Paweena Traiperm (Kew Bulletin, 2020)

A revision of the genus Gouania (Rhamnaceae) in the Philippines and Sundaland - Daniel Cahen; Kurt S. Stenn; Timothy M. A. Utteridge (Kew Bulletin, 2020)
Summary The climbing genus Gouania (Rhamnaceae) is revised in western Malesia. Five species are recognised for the Philippines and Sundaland using morphological evidence, including a new species from the Philippines: Gouania longipedunculata . A taxonomic treatment, including a preliminary IUCN conservation status assessment, is presented for each species.

Editorial - Timothy Utteridge (Kew Bulletin, 2020)

Diplycosia papuana (Ericaceae: Vaccinioideae: Gaultherieae): a new endemic species from central New Guinea - Wendy A. Mustaqim; Timothy M. A. Utteridge; Charlie D. Heatubun (Kew Bulletin, 2019)
Summary Diplycosia papuana (Ericaceae: Vaccinioideae: Gaultherieae), a new endemic species from central New Guinea, is described and illustrated here. Notes on the distribution, ecology and conservation status of the new species, as well as a consideration of closely related species, are provided.

An enigmatic genus on an enigmatic island: the re‐discovery of Kalappia on Sulawesi - Liam A. Trethowan; Asrianti Arif; Ruth P. Clark; Deden Girmansyah; Endang Kintamani; Chrissie J. Prychid; Niken Pujirahayu; Rosmarlinasiah; Francis Q. Brearley; Timothy M. A. Utteridge; Gwilym P. Lewis (Ecology, 2019)

Maesa camptobotrys (Primulaceae) is Sabia pauciflora (Sabiaceae), not Discocalyx (Primulaceae) - Timothy M. A. Utteridge (Kew Bulletin, 2019)
Summary The type specimen of Maesa camptobotrys is re-examined and morphology and characters are discussed. The specimen is a member of the genus Sabia (Sabiaceae) rather than the genus Discocalyx (Primulaceae) into which it was transferred; the name is formally placed as a synonym of Sabia pauciflora .

A linear sequence to facilitate curation of herbarium specimens of Annonaceae - Lars W. Chatrou; Ian M. Turner; Bente B. Klitgaard; Paul J. M. Maas; Timothy M. A. Utteridge (Kew Bulletin, 2018)

Editorial - Timothy Utteridge (Kew Bulletin, 2018)

A synopsis of the genus Smythea (Rhamnaceae) - Daniel Cahen; Timothy M. A. Utteridge (Kew Bulletin, 2018)

Editorial - Timothy Utteridge (Kew Bulletin, 2017)

A revision of the genus Systellantha B. C. Stone. Studies in Malaysian Myrsinaceae IV - Clare Drinkell; Timothy M. A. Utteridge (Kew Bulletin, 2015)

A synopsis of the genus Embelia in Peninsular Malaysia and Singapore. Studies in Malaysian Myrsinaceae III - Anne Dubéarnès; Avelinah Julius; Timothy M. A. Utteridge (Kew Bulletin, 2015)

An updated and revised description of Timonius grandifolius (Rubiaceae: Guettardeae) and a new character observation for the tribe Guettardeae. Contributions to the Flora of Mt Jaya, XIX - Marie Briggs; Timothy M. A. Utteridge (Kew Bulletin, 2014)

Ardisia silamensis, a new ultramafic species from Borneo; studies in Malaysian Myrsinaceae II - Timothy M. A. Utteridge; Avelinah Julius; Suzana Sabran (Kew Bulletin, 2014)

A revised circumscription of Maesa ruficaulis S. Moore (Primulaceae-Maesoideae). Contributions to the Flora of Mt Jaya, XVIII - Timothy M. A. Utteridge (Kew Bulletin, 2013)

Six new species and a new subspecies of Gomphandra (Stemonuraceae) from the Philippines - Melanie Schori; Timothy M. A. Utteridge (Kew Bulletin, 2012)

Four new species of Maesa Forssk. (Primulaceae) from Malesia - Timothy M. A. Utteridge (Kew Bulletin, 2012)

Revision of Ardisia subgenus Bladhia in Peninsular Malaysia; studies in Malaysian Myrsinaceae I - Avelinah Julius; Timothy M. A. Utteridge (Kew Bulletin, 2012)

A revision of the genus Medusanthera (Stemonuraceae, Icacinaceae s.l.) - Timothy M. A. Utteridge (Kew Bulletin, 2011)

A new species of Platea (Icacinaceae) from Peninsular Malaysia: Platea malayana - Timothy M. A. Utteridge (Kew Bulletin, 2010)

Two new combinations in Pyrostria (Rubiaceae, Vanguerieae) from Thailand - Timothy M. A. Utteridge; Aaron P. Davis (Kew Bulletin, 2009)

Stemonurus corrugatus (Stemonuraceae, Icacinaceae s.l.) a new species from Sarawak - Timothy M. A. Utteridge; Melanie Schori (Kew Bulletin, 2009)